Factors that promote and sustain the use of traditional, complementary and integrative medicine services at LEKMA hospital, Ghana, 2017: an observational study - Angela Kenu; Ernest Kenu; Delia Akosua Bandoh; Moses Aikins (BMC, 2021)
Abstract Background About 70% of Ghanaians depend on traditional, complementary and integrative medicine (TCIM) practices for primary healthcare needs. It was therefore integrated into mainstream healthcare delivery system by the Ministry of Health in September 2012. LEKMA hospital was one of the institutions for piloting TCIM services. We assessed factors that promote the usage and sustainability of TCIM services within the formal healthcare system. Methods We conducted a cross-sectional study from April-June 2017 at the LEKMA hospital, Accra, Ghana. Patients and managers of TCIM clinic were interviewed. Data was collected through qualitative and quantitative approaches. We defined usage of TCIM as its current use, and sustainability as structures in place to run TCIM services. For assessing usage, a five-point Likert scale was used to assess five domain areas via exit interviews. Managers were assessed on the sustainability of TCIM services through in-depth interviews. Likert scales responses were analysed quantitatively using descriptive tertile statistics. Thematic analysis was used for qualitative analysis. Results Overall, 72.7% (40/55) of the clients showed a high preference for TCIM usage and 80.0% (4/5) of the managers valued it as partially sustainable. Eighty per cent (44/55) of patients indicated that the location of TCIM services and availability of visible directional signs influenced the good usage; 84% (46/55) of the patients agreed that the usage of TCIM was influenced by their perceived effectiveness. Managers indicated that human resources for providing services was a challenge and TCIM integration into the operations of the hospital needed to be improved. Conclusion We observed a high preference for usage of TCIM among users at LEKMA hospital. The general belief in the potency, perceived effectiveness, location and availability of TCIM services are key determinants of the high preference for usage of TCIM. Provision of TCIM services in its current form is partially sustainable from the managers' perspective. We recommend that the Ministry of Health ensures the availability of staff and create awareness of TCIM services among the general populace.